Comprehensive analysis of innovative devices based on shape memory alloys in food technology apparatuses - Ukrainets, Anatoliy; Shesterenko, Volodymyr; Romaniuk, Volodymyr (My University, 2020)
Ця робота містить комплексний аналіз інноваційних пристроїв на базі сплавів з ефектом пам’яті форми (ЕПФ) для застосування в апаратах харчової промисловості. Використовувались фізичне та математичне моделювання процесів, положення теорії автоматичного керування, теорія нечіткої логіки. Проведений комплексний аналіз пристроїв на основі матеріалів з ЕПФ, які можуть бути застосовані в апаратах харчової промисловості. Зокрема проаналізована конструкція та принцип дії термоклапанів, що вирізняються простотою конструкції та надійністю; індикатора критичного підвищення температури корпусу апарата та гайки сигналізатора аварійного перегрівання роз’ємного корпусу технологічної установки, які підвищують надійність роботи апаратів; термопривода, який може бути ефективно використаний на підприємствах, де виникає потреба утилізувати низькотемпературну теплову енергію та геліопривода. Конструкція індикатора критичного підвищення температури роз’ємного корпусу технологічної установки відзначається високою технологічністю та надійністю. На багатьох підприємствах виникає потреба утилізувати теплову енергію при порівняно невеликому перепаді температур. Цим вимогам відповідає конструкція термонасосу. Силові елементи на основі сплавів з ЕПФ мають суттєві переваги: меншу масу, робота в широкому діапазоні температур, незначні габарити, плавне переміщення робочих органів, меншу вартість, високу чутливість. Приводи на основі термочутливих елементів з ЕПФ ефективні в сонячних енергоустановках.

This study contains a comprehensive analysis of innovative devices based on shape memory alloys for use in food technology apparatuses. Physical and mathematical processes modeling, principles of the theory of automatic control, the theory of fuzzy logic were used. The complex analysis of devices based on materials with shape memory effect (SME), which can be applied to food industry apparatuses, was conducted. In particular, design and principle of operation of the thermal valves, characterized by simplicity of construction and reliability, were analyzed. Design and principle of operation of the critical temperature increase indicator for machine's casing and the nut-indicator for overheating of sectional casing of technological machine, which increase the reliability of apparatuses were analyzed. Design and principle of operation of the thermal drive which can be effectively used in factories that need to utilize low-temperature thermal energy were analyzed. Design and principle of operation of the heliodrive were analyzed. Design of the critical temperature increase indicator for machine's casing is highly technological and reliable. Many factories need to utilize heat energy at relatively low temperature difference. These requirements are met by the design of the thermal drive. Power elements based on SME alloys have significant advantages: less mass, they can work in a wide temperature range, they have small dimensions, smooth movement of working parts, lower cost, high sensitivity. Drives based on heat-sensitive elements with SME are effective in solar power installations.
Keywords: термопривід; термоклапан; геліопривід; thermal drive; thermal valve; heliodrive; кафедра електропостачання і енергоменеджменту